2013
DOI: 10.1007/s00223-013-9721-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Food-Frequency Questionnaire for the Assessment of Calcium Intake in Schoolchildren Aged 9–10 Years

Abstract: Bone mass increases steadily until age 20-30 years, when peak bone mass (PBM) is acquired. Nutrition plays a critical role in achievement of the optimal genetically programmed PBM, with reduction in the risk of osteoporosis later in life. Intake of nutrients can be estimated through the use of various tools; typically, food-frequency questionnaires (FFQs) are used in epidemiologic studies. The aim of this study was to validate a 21-item, semiquantitative FFQ to assess important nutrient intakes for bone health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
15
2
Order By: Relevance
“…While most studies have found FFQ to be reliable in dietary Ca assessment, it is however not possible to compare these studies as FFQs used are different and so are the methods of assessment through food diaries. Previous studies, which have used FFQ to estimate dietary Ca intake, have tended to overestimate the daily dietary Ca 5 6. In contrast, the results of our study showed that FFQ underestimated the daily dietary Ca intake in children.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…While most studies have found FFQ to be reliable in dietary Ca assessment, it is however not possible to compare these studies as FFQs used are different and so are the methods of assessment through food diaries. Previous studies, which have used FFQ to estimate dietary Ca intake, have tended to overestimate the daily dietary Ca 5 6. In contrast, the results of our study showed that FFQ underestimated the daily dietary Ca intake in children.…”
Section: Discussioncontrasting
confidence: 87%
“…Validation of other FFQs for dietary Ca intake in children have previously been performed, albeit, in different populations 5 6. While most studies have found FFQ to be reliable in dietary Ca assessment, it is however not possible to compare these studies as FFQs used are different and so are the methods of assessment through food diaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it has been reported that FFQs tend to overestimate actual intake, compared to other dietary assessments such as two 24-h food recall (45,46) , 2-day food diary (47) and 3-day food record (48) , as well as 7-day weighed records (49) . In context of the present study, only a single study of Belgian school-aged children (12-15 years) has compared a FFQ with a 7-day food diary (50) .…”
Section: Discussionmentioning
confidence: 99%
“…The 3-day prospective diet diary/food intake record is considered "gold standard" against which other dietary assessment methods are compared, but can be time consuming to administer and assess. FFQs tend to overestimate daily dietary nutrient intake, although this depends on the number of food categories included in the tool [53][54][55]. Supplemental Table 3 lists the relative advantages and disadvantages of the different methods of dietary assessment.…”
Section: Evidence and Rationalementioning
confidence: 99%